APPLICATION OF IMAGE PROCESSING TO EDUCATIONAL PHYSICS EXPERIMENTS AND INTERDISCIPLINARY STUDENT MOTIVATION - Macerauskas, Eugenijus; Lucun, Andzej; Tumasonis, Romanas; Kirdeikiene, Aliona; Kozic, Antoni; Cetyrkovski, Slavomir (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The paper presents an automated educational system for fast physics experiments using image processing technologies. The article shows how image processing techniques help students perform better in physical physics experiments and obtain more accurate results compared to traditional methods. The experimental system used image processing technologies, programming in LabVIEW View, automated data recording, and image processing of experimental results using MATLAB. The experimental system demonstrates students' professional specializations such as mechatronics, mathematics, and programming. The developed system allowed to improve the precision of mechanics experiments reduced the time needed to experiment and allowed automatic processing of the data accounting. The experimental physics laboratory system has already attracted specific student interest and, according to the author practice, has increased student motivation as students see realistic prospects for their future abilities. The system was created by higher education students, and  includes physics, image processing technologies, not only the knowledge of electronic engineering specialization but also programming knowledge. Students of the final courses designed the experimental system, and the physics course experiments are carried out in the first course, showing collaboration between different professions and different course students, knowledge adaptability, and interdisciplinary ties.